Shopping and business centres in Sarajevo - Nurković, Rahman (Journal for Geography, 2012)
In the paper, influence of shopping and business centres: Mercator, Tuš, Obi Robot, Konzum and BBI on development of Sarajevo city is analysed. Results of the survey made among visitors indicate to presence of social functions (walk, leisure, recreation, fun, socialization) in five centres. The mentioned functions are more expressed in new shopping centres, while shopping is the most important motive of visits to commercial centres. Sarajevo city makes, with its surrounding, a functionally connected wholeness – city, respectively an urban region.
Keywords: shopping and business centres; central business centre; public space; social functions; Sarajevo